FEATURES OF TEMPORAL CHANGES OF FORMALDEHYDE CONCENTRATIONS IN THE AIR OF UKRAINIAN CITIES - Сніжко, С.; Шевченко, О.; Яценко, Ю.; Данілова, Н. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
Main formaldehyde emissions sources in big cities have been analyzed in the article. The temporal dynamics of average concentrations of formaldehyde in the air of Donetsk, Kyiv, Lutsk, Nikolayev and Uzhgorod for a long period of time is shown. The annual variation of formaldehyde concentrations in these cities has been studied. The comparative analysis of air pollution by formaldehyde in cold and warm seasons has been conducted. Keywords: air pollution, formaldehyde, dynamics of concentrations changes.